Application of Valance Framework and D&M IS Success Model to Analyze Determinant Factors of Intention to Use E-Commerce Services for Sellers - Sudirjo, Frans; Misrofingah; Sofyanty, Devy; Fikri Maulana, Muhammad; Widia Nurdiani, Tanti (SEULANGA SYSTEM PUBLISHER, 2023)
Finding out what influences’ MSMEs' (small and medium-sized enterprises) desire to use e-commerce is the goal of this research. This study employed a quantitative methodology. A survey and the indirect distribution of questionnaires served as the data collection methods. MSMEs who currently use e-commerce as a sales channel received questionnaire data. The MSMEs in large cities that have used e-commerce as a sales channel make up the population of this study. Purposive sampling is a non-probability sampling technique that was employed by the researcher. The investigator made the decision to employ a 200-sample maximum. In this study, the PLS-SEM program SmartPLS was used for data analysis. An outer model analysis and an inner model analysis were performed. Several conclusions can be drawn from this research, including the fact that perceived benefit is the factor that influences MSMEs' intentions the most. As a result, sellers who have experienced the benefits will be more inclined to use e-commerce. Two of the hypotheses are not accepted. This is due to the fact that MSME actors must engage in e-commerce, meaning that quality and service have no bearing on their goals. The theory that has the biggest impact is that trust is influenced by system quality. Thus, it can be said that MSME participants have more faith in the system the higher its quality.